Control gerencial: El costo de adquisición de equipos y controles en una unidad hospitalaria - Pinheiro de Sá, Luciano (2024)
The acquisition cost of every equipment is connected to the complexity degree of the operation, leading to possible differences among the assigned controls. Variations in control practices are likely to be more complex depending on the organizations, as in the case of hospital units. The paper aimed to control a hospital unit based on the asset acquisition cost and considering contingency factors. Management control is understood as a set of activities and practices to guarantee the enforcement of management plans (Anthony Govindarajan, 2008). A single-case study qualitative approach was used and data was collected from semi-structured interviews. The object was a hospital in Brazil. The asset acquisition cost did not seem to interfere with the control practices adopted by the hospital unit. In this manner, the organization assets are recorded and controlled uniformly. In spite of a formal and structured internal control, an asset having a higher or lower acquisition cost does not directly interfere with control.